2019
DOI: 10.3389/fgene.2019.00310
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Maximal Lifespan and High Bone Marrow Chimerism After Nonmyeloablative Syngeneic Transplantation of Bone Marrow From Young to Old Mice

Abstract: The goal of this work was to determine the effect of nonablative syngeneic transplantation of young bone marrow (BM) to laboratory animals (mice) of advanced age upon maximum duration of their lifespan. To do this, transplantation of 100 million nucleated cells from BM of young syngeneic donors to an old nonablated animal was performed at the time when half of the population had already died. As a result, the maximum lifespan (MLS) increased by 28 ± 5%, and the survival time from the beginning of the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These findings are consistent with the results of the pilot study with i.c.v. infusion of bone marrow‐derived mouse stem cells obtained from mutants expressing green fluorescent protein (GFP) (see Data S1; Figure S3,)These experiments showed that i.c.v. administration of Neuro‐Cells to mice at the concentrations 100 000‐500 000 is well tolerated.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with the results of the pilot study with i.c.v. infusion of bone marrow‐derived mouse stem cells obtained from mutants expressing green fluorescent protein (GFP) (see Data S1; Figure S3,)These experiments showed that i.c.v. administration of Neuro‐Cells to mice at the concentrations 100 000‐500 000 is well tolerated.…”
Section: Methodsmentioning
confidence: 99%
“…4a). This higher number of donor HSCs allowed on average equal high engraftment of recipients of both aged and CASIN mice, excluding that differences in engraftment levels or a low engraftment level would bias the survival outcome 53 (Fig. 6b).…”
Section: Casin Treatment Restores a Youthful Transcriptional Heteroge...mentioning
confidence: 98%
“…It is the delivery method and subsequent stable engraftment of these cells to the bone marrow that is the limiting factor in moving this type of cell therapy from the lab to the clinic. To circumvent the toxic effect of radiation, other models of HSC replacement therapy have been proposed including nonmyeloablative transplantation, anti-cKit and anti-CD47 antibody-mediated HSC depletion or mobilization based-transplant [215][216][217]. In nonmyeloablative transplantation, the therapy relies on our understanding that the signals which retain HSCs to the niche are defective with age [107].…”
Section: Bone Marrow Transplant and Niche Remodelingmentioning
confidence: 99%
“…While the strategy can extend rodent lifespan, the efficacy is still low, potentially because of the age-related expansion of bone marrow MSCs [124]. However, using this approach, Kovina et al showed that transplantation of whole BM, not just purified HSCs, resulted in 28% chimerism 6 months post-transplant [215]. They attributed this high rate of chimerism to the age of the recipient (B10-GFP mice, 15 months old).…”
Section: Bone Marrow Transplant and Niche Remodelingmentioning
confidence: 99%